2015
DOI: 10.1242/jeb.129486
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high salt exposure on cardiovascular development in the early chick embryo

Abstract: In this study, we show that high-salt exposure dramatically increases chick mortality during embryo development. As embryonic mortality at early stages mainly results from defects in cardiovascular development, we focused on heart formation and angiogenesis. We found that high-salt exposure enhanced the risk of abnormal heart tube looping and blood congestion in the heart chamber. In the presence of high salt, both ventricular cell proliferation and apoptosis increased. The high osmolarity induced by high salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…In our previous, we have found that excess ROS affected cell proliferation, as well as apoptosis and resulted in embryonic cardiovascular dysplasia (Wang et al, ). To further explore whether the influence of excess ROS on proliferation and apoptosis, we employed the H9c2 cells cultured in vitro in presence of high salt.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In our previous, we have found that excess ROS affected cell proliferation, as well as apoptosis and resulted in embryonic cardiovascular dysplasia (Wang et al, ). To further explore whether the influence of excess ROS on proliferation and apoptosis, we employed the H9c2 cells cultured in vitro in presence of high salt.…”
Section: Resultsmentioning
confidence: 93%
“…For the Vitamin C (VC) −treated embryos, the HH0, HH4, or HH7 chick embryos in EC culture were incubated with 2.86 mM VC (Beijing Ding Guo Chang Sheng, China) according to experimental requirements. Chick embryo treatment of VC is 0.5 mg/egg (Li et al, ; Wang et al, ). In EC‐culture, it is 1 ml/embryo, so the final concentration is 2.86 mM (=0.5 mg/ml) in culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…High salt has been shown to increase the production of reactive oxygen species leading to impaired nitric oxide signaling, arterial stiffening, and vasoconstriction (Banday, Muhammad, Fazili, & Lokhandwala, ; Bayorh, Ganafa, Socci, Silvestrov, & Abukhalaf, ; Dobrian et al, ; Trolliet, Rudd, & Loscalzo, ). In hypertensive models with enhanced oxidative stress such as in high‐salt induced hypertension, renal expression of SOD has been found to be increased to cope with the increase in superoxide production (Sainz et al, ; Vaziri, Lin, Farmand, & Sindhu, ; Y. Wang, Chen, & Wang, ; G. Wang et al, ). Herein, high‐salt diet induced an increase in the expression of CuZn‐SOD and Mn‐SOD that was concomitant with the increase of urinary RNA/DNA damage markers.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiovascular system is the first system to emerge during embryonic development and plays critical roles in the distribution of blood to various tissues to fulfill oxygen and nutrient requirements. This system is composed of the heart and the vascular system, which are derived from the embryonic mesoderm and extraembryonic yolk sac ( Wang et al., 2015a ). The formation of the heart is a complex morphogenetic process that depends on the spatiotemporally regulated contribution of cardiac progenitor cells ( Vincent and Buckingham, 2010 ).…”
Section: Introductionmentioning
confidence: 99%